Методологія розрахунку економічної доцільності інноваційного розвитку виробництва губчастого феровольфраму у вітчизняній металургії - Григор’єв, С.М.; Яковлєв, Д.В. (Physico-technological Institute of Metals and Alloys, 2026)
This study presents a comprehensive methodology for assessing the economic feasibility of implementing innovative production of sponge ferrotungsten (SFTG) in the domestic metallurgical industry using powder metallurgy methods. The proposed technology is aimed at fundamentally optimizing the consumption of scarce resources and energy by fully or partially replacing expensive reducing agents, such as silicon and aluminum powders, with dispersed carbon-containing industrial waste. This allows not only to reduce the cost of the product, but also to simplify the hardware design of the melting process. The use of SFTG as an innovative alloying additive in the smelting of high-speed steel (using the example of the P6M5 grade) provides a qualitatively new level of alloying efficiency. Due to the high specific surface area and developed porosity of the "sponge", the time for dissolving tungsten in the melt is reduced, which minimizes the oxidation potential of the bath and reduces irreversible losses of other alloying elements. The paper details a mathematical model of economic calculation based on a cross-sectional analysis: from reducing material consumption at the oxide reduction stage to increasing the productivity of electric arc furnaces DSV-25. Particular attention is paid to the thermodynamic criteria for tungsten absorption, which is 5-7 times higher than that of traditional fused ferrotungsten. The economic effect is confirmed by calculations using current London Metal Exchange (LME) quotes. The results of the study prove that the introduction of FVG production is a strategically important step for import substitution and increasing the competitiveness of domestic special steels on the world market in the context of the energy crisis.